2016
DOI: 10.48550/arxiv.1609.07775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biunitary constructions in quantum information

Abstract: We present an infinite number of construction schemes involving unitary error bases, Hadamard matrices, quantum Latin squares and controlled families, many of which have not previously been described. Our results rely on biunitary connections, algebraic objects which play a central role in the theory of planar algebras. They have an attractive graphical calculus which allows simple correctness proofs for the constructions we present. We apply these techniques to construct a unitary error basis that cannot be b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…The current authors have previously shown that CQM methods can be extended to a highercategorical setting [54,63,64], developing the work of Baez on a categorified notion of Hilbert space [7], and this paper develops these ideas further.…”
Section: Related Workmentioning
confidence: 91%
See 3 more Smart Citations
“…The current authors have previously shown that CQM methods can be extended to a highercategorical setting [54,63,64], developing the work of Baez on a categorified notion of Hilbert space [7], and this paper develops these ideas further.…”
Section: Related Workmentioning
confidence: 91%
“…The graphical notation we employ can be described formally as a shaded planar algebra, although we do not use that terminology in this paper, preferring a more elementary presentation. The relationship between shaded planar algebras and Hadamard matrices was first suggested by Jones [34], and developed by the present authors [54,63,64].…”
Section: Related Workmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, it has naturally led to the problem of axiomatising fragments of quantum theory as independent higher algebraic theories: once we have packaged such a fragment into a theory, we can study it and tweak it on its own, forgetting the context from which it came, and gaining new perspective from its interpretation in different contexts. Examples include the theory of biunitaries, which underlies several constructions in quantum information theory [RV16], but also classical cryptography with "one time pads" [SV13]; the various theories called "ZX calculi", axiomatisations of fragments of the theory of qubits, including stabiliser quantum mechanics [Bac14a]; and our own ZW calculus [Had15], the subject of Chapter 5, towards which we will be working in this chapter.…”
Section: From Abelian Groups To Hilbert Spacesmentioning
confidence: 99%